Making Adhān or Knocking Bangzi: Sonic Expressions of Jahriyyah Group in Contemporary China (Laungan Azan menggunakan Ketukan Bangzi: Ekxpresi Sonic Tari-kat Jahriyyah di China Kontemporari) - Ma Qiang; Ma Xinguo, (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
Bangzi is a kind of wooden clappers. It was once used by watchmen for time announcement and for indicating danger during emergencies. Jahriyyah, a distinguished Islamic Sufi group in China, was officially labelled as a heterodox Islamic faction because of its rebellion against the government. The rebellion was ignited by a religious dispute between the Huasi faction (a Sufi group of the Hufiyyah order) during the Qianlong period of the Manchu-led Qing dynasty. Due to its stigmatization as a “New Faction” during this rebellion, Jahriyyah’s religious activities were conducted secretly. Knocking bangzi instead of the traditional human voice for the call to prayer has become a tradition for Jahriyyah, and the current adherents consider such tradition as “orthodox”, and are therefore reluctant to change it. This paper explores Jahriyyah’s conception of their sonic heritage and suggests that two contextualized dimensions should be taken into account when interpreting the transformation and expression of Islamic factions in China today: first, the political impact of post-Mao policies; and second, the impact of the post-shaykh, or post-factional, era. Keywords: Jahriyyah, Adhān, Islam; Adjustment, Transformation. Abstrak Bangzi merupakan sebuah blok kayu. Ia pernah digunakan oleh pengawas sebagai alat pengumuman dan sebagai alat amaran bahaya semasa kecemasan. Jahriyyah, merupakan tarekat Sufi Islam yang terkenal di China, telah dilabel secara rasmi sebagai puak faksi Islam heterodoks kerana pemberontakannya terhadap kerajaan. Pemberontakan itu disebabkan oleh perselisihan agama antara puak Huasi (kumpulan Sufi di bawah gerakan Hufiyyah) pada zaman pemerintahan Maharaja Qianlong daripada dinasti Qing yang dipimpin oleh Manchu. Kerana stigmatisasinya sebagai "Faksi Baru" semasa pemberontakan ini, kegiatan keagamaan Jahriyyah telah dijalankan secara sembunyi. Memukul bangzi sebagai cara menggantikan azan telah manjadi tradisi tarekat Jahriyyah.dimana para pengikut sekarang menganggap tradisi tersebut merupakan amalan "ortodoks", dan enggan menukarnya dengan amalan lain. Makalah ini menerangkan konsepsi Jahriyyah tentang warisan sonik mereka dan mencadangkan bahawa dua dimensi kontekstualisasi harus diambil kira apabila menafsirkan transformasi dan ekspresi puak Islam di China hari ini: pertama, kesan politik dasar post-Mao; dan kedua, kesan post-shaykh, atau post-faksi, era. Kata Kunci: Jahriyyah, Azan, Islam, Pemindahan, Transformasi.